TMED3/RPS15A Axis promotes the development and progression of osteosarcoma - Wei Xu (BMC, 2021)
Abstract Background Osteosarcoma is a primary malignant tumor that mainly affects children and young adults. Transmembrane emp24 trafficking protein 3 (TMED3) may be involved in the regulation of malignant cancer behaviors. However, the role of TMED3 in osteosarcoma remains mysterious. In this study, the potential biological function and underlying mechanism of TMED3 in progression of osteosarcoma was elaborated. Methods The expression of TMED3 in osteosarcoma was analyzed by immunohistochemical staining. The biological function of TMED3 in osteosarcoma was determined through loss-of-function assays in vitro. The effect of TMED3 downregulation on osteosarcoma was further explored by xenograft tumor model. The molecular mechanism of the regulation of TMED3 on osteosarcoma was determined by gene expression profile analysis. Results The expression of TMED3 in osteosarcoma tissues was significantly greater than that in matched adjacent normal tissues. Knockdown of TMED3 inhibited the progression of osteosarcoma by suppressing proliferation, impeding migration and enhancing apoptosis in vitro. We further validated that knockdown of TMED3 inhibited osteosarcoma generation in vivo. Additionally, ribosomal protein S15A (RPS15A) was determined as a potential downstream target for TMED3 involved in the progression of osteosarcoma. Further investigations elucidated that the simultaneous knockdown of RPS15A and TMED3 intensified the inhibitory effects on osteosarcoma cells. Importantly, knockdown of RPS15A alleviated the promotion effects of TMED3 overexpression in osteosarcoma cells. Conclusions In summary, these findings emphasized the importance of TMED3/RPS15A axis in promoting tumor progression, which may be a promising candidate for molecular therapy of osteosarcoma.